Underground allies: How and why do mycelial networks help plants defend themselves?. (15th October 2013) - Babikova, Zdenka; Johnson, David; Bruce, Toby; Pickett, John; Gilbert, Lucy
<x xml:space="preserve">Abstract</x> Most land plants associate with mycorrhizal fungi that can connect roots of neighboring plants in common mycelial networks (CMNs). Recent evidence shows that CMNs transfer warning signals of pathogen and aphid attack between plants. However, we do not know how defence‐related signaling via CMNs operates or how ubiquitous it is. Nor do we know what the ecological relevance and fitness consequences are, particularly from the perspective of the mycorrhizal fungus. Here, we focus on the potential fitness benefits for mycorrhizal fungi and outline hypothetical scenarios in which signal transfer via CMNs is modulated in order to acquire the most benefit for the fungus (i.e. acquisition of carbon) for minimal cost. We speculate that the signal may be quantitative and may elicit plant defence responses on different levels depending on the distance the signal is transferred. Finally, we discuss the possibility of practical applications of this phenomenon for crop protection.